Pengaruh Kelompok UMKM Ternak Lele terhadap Peningkatan Pendapatan Masyarakat Desa Ulapato - Asral Kelvin Sahrain (Jurnal Ekonomi Islam, 2025)
This study aims to analyze the influence of MSME groups (catfish farming) on increasing community income in Ulapato Village, Gorontalo Regency. Catfish farming has become one of the promising business sectors in rural areas, especially with the support of MSME group-based management. This research uses a quantitative approach with a survey method involving 80 respondents who are members of the catfish farming MSME group. Data were collected through questionnaires and interviews, then analyzed using simple linear regression analysis. The results showed that the catfish farming MSME group had a significant positive effect on increasing community income, with a regression coefficient of 0.758 and an R² value of 0.574, meaning that 57.4% of income variation could be explained by participation in the MSME group. The factors that influence include access to capital, production technology, marketing networks, and knowledge of catfish farming management. This study concludes that the existence of MSME groups plays an important role in improving the economic welfare of rural communities through increased income, skill development, and business network expansion.